A Generalized Group Communication Network Stack and its Application to Hybrid Multicast - Matthias Wählisch and Thomas C. Schmidt and Georg Wittenburg (IEEE, 2009)
Group communication services are most efficiently implemented on the lowest layer available. Network layer multicast transparently delegates group distribution to the link layer wherever possible. Native multicast deployment, though, has been mainly limited to 'walled gardens' within provider domains. Overlay multicast overcomes these deployment restrictions on the price of a performance penalty. Current activities focus on hybrid approaches which dynamically combine multicast in overlay and underlay, and adaptively optimize group communication. The basic requirement for such a flexibly deployable architecture is a layer-transparent group communication stack that integrates variable multicast protocols by a common API. In this paper, we present a common group communication stack which serves the requirements of data distribution and maintenance for multicast and broadcast on a middleware abstraction layer, suitable for underlay and overlay communication. We discuss its application in the context of hybrid multicast schemes.